2018
DOI: 10.21608/mjcu.2018.55054
|View full text |Cite
|
Sign up to set email alerts
|

Subclinical Right Ventricular Dysfunction in Type 2 Diabetes Mellitus: An Echocardiographic Strain/Strain Rate Study

Abstract: Background: Type II Diabetes Mellitus (DM) was accompanied by subclinical impairment of Right Ventricular (RV) systolic dysfunction. Two-Dimensional (2D) Speckle Tracking Echocardiography (STE) allows a precise evaluation of myocardial function. Aim of the Study: The aim of this study was to assess the RV systolic function in asymptomatic normotensive subjects with type II DM compared with control subjects, using strain/ strain rate qualification by 2D STE. Subjects and Methods: Prospective study enrolled 100 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…In our study, there was a significantly higher A velocity in diabetic patients but not an E velocity. In the study conducted by Yaser R. Mohammed et al, 22 they demonstrated the presence of subclinical RV as well as LV dysfunction in diabetes mellitus. A study published in 2020 concluded that prediabetes is associated with structural and functional changes in the right atria and ventricle due to the direct myocardial impact of hyperglycemia.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…In our study, there was a significantly higher A velocity in diabetic patients but not an E velocity. In the study conducted by Yaser R. Mohammed et al, 22 they demonstrated the presence of subclinical RV as well as LV dysfunction in diabetes mellitus. A study published in 2020 concluded that prediabetes is associated with structural and functional changes in the right atria and ventricle due to the direct myocardial impact of hyperglycemia.…”
Section: Discussionmentioning
confidence: 94%
“…Similar subclinical RV as well as LV dysfunction was found in a study published by Waler R Hablas et al in 2018 in Egypt. 22 In a study conducted by Aymen Ahmed et al, 23 indices of RV function, i.e., peak myocardial systolic velocity, early diastolic myocardial velocity, and late diastolic myocardial velocity, as measured by tissue Doppler imaging, were found to be significantly lower in diabetics compared to the control group. A similar result has been obtained in our study, where all four parameters measured through TDI showed significant differences among the diabetic and nondiabetic groups.…”
Section: Discussionmentioning
confidence: 94%